Regional Human Rights Protection Systems – Introduction - Szalayné Sándor , Erzsébet (Children’s Rights in Regional Human Rights Systems, 2024)
When discussing human rights, we specifically refer to the protection that international law guarantees to individuals (and groups) – including children – through international treaties and other mechanisms. It should be emphasised that the idea of limiting the power of the state over the individual is much older than these international legal mechanisms. Human rights are, therefore, a cross-cutting issue regulated not only by international law but also, and above all, by domestic law. International human rights protection differs from traditional international law in many ways and covers a wide range of issues. In addition to the development of international human rights protection, this article outlines the basis for understanding human rights, characteristics of human rights obligations, and possibilities for limiting them. Keywords: international law, concept of human rights, generations of human rights, universality of human rights, indivisibility of human rights, obligation to respect, obligation to protect, obligation to fulfil, The International Bill of Rights, leading human rights treaties, United Nations human rights bodies, Council of Europe, European Court of Human Rights, monitoring bodies, fundamental rights in the European Union, African Union, Organization of American States